A model for measuring organizational innovativeness in the housebuilding industry - Kamaruddeen, Ahmed Mohammed; Yusof, Nor Aini; Said, Ilias; Zainul Abidin, Nazirah (2008)
Series of criticisms have been leveled at the construction industry for the slow in innovativeness, Abandonment of Government projects; shoddy works, not being environmentally conscious and so forth. For the industry to sustain itself over the next decade, a change in mindset and the way of doing business is fundamental. This has call for research on the organizational innovativeness of the house building industry in Malaysia. Innovation is a complex and systemic process, which is hardly captured in its totality through indicators of input and output. A couple of methods for measuring organizational innovativeness have been identified in the literature. However, none of these methods has been adopted for measuring the organizational innovativeness of the housing developers. The Oslo manual for innovation survey is the most widely used instrument for large scale innovation surveys, it recognize that dissemination mechanisms and incremental change account for most of the innovation occurring in developing countries, owing to the particular characteristics of the society and the economy in many of these countries which influence innovation processes in many ways. How ever, its adoption for measuring firm innovation in developing countries has been criticized. This paper attempts to suggest the most appropriate instrument for the measurement of organizational innovativeness in the house building industry.